1993
DOI: 10.1093/infdis/167.6.1418
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of High-Titer Edmonston-Zagreb Measles Vaccine in Human Immunodeficiency Virus-Infected Children in Kinshasa, Zaire

Abstract: The response to Edmonston-Zagreb vaccine (titer, 5.4 log10 pfu) was evaluated among children in a study of perinatal transmission of human immunodeficiency virus (HIV) in Kinshasa. Acute postvaccination adverse events were monitored for 49 HIV-infected and 376 non-HIV-infected infants, and measles antibody responses were assessed by ELISA for 34 HIV-infected and 255 non-HIV-infected infants. There was no increase in the incidence of common symptoms 7-10 days after vaccination. HIV-infected infants were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
2
19
0
2
Order By: Relevance
“…Our study also demonstrated a higher seroprevalence of measles antibodies in HIV infected as compared to HIV-uninfected exposed infants. This observation was in concordance with reports by Cutts et al 24 (11.8% of HIV-infected and 6.5% of HIV-exposed uninfected infants), Rudy et al 25 (16.7% of HIV-infected and 0% of HIV-exposed uninfected infants) and Lepage et al 22 (15% of HIV-infected and 10% of HIV-exposed uninfected infants). The possible explanation for apparent longer persistence of maternally acquired measles antibodies among HIV-infected infants may be the presence of polyclonal B-cell activation and hypergammaglobulinemia in these infants giving rise to false positive test results 26 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study also demonstrated a higher seroprevalence of measles antibodies in HIV infected as compared to HIV-uninfected exposed infants. This observation was in concordance with reports by Cutts et al 24 (11.8% of HIV-infected and 6.5% of HIV-exposed uninfected infants), Rudy et al 25 (16.7% of HIV-infected and 0% of HIV-exposed uninfected infants) and Lepage et al 22 (15% of HIV-infected and 10% of HIV-exposed uninfected infants). The possible explanation for apparent longer persistence of maternally acquired measles antibodies among HIV-infected infants may be the presence of polyclonal B-cell activation and hypergammaglobulinemia in these infants giving rise to false positive test results 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Despite measles being a live-attenuated vaccine, none of our infants had any serious adverse effects associated with vaccination. Some other studies 22 24 where a high titre measles vaccine was used also reported similar low incidence of adverse effects with no serious or life-threatening adverse effect to be associated with measles vaccine. In a systematic review and meta-analysis on safety and immunogenicity of measles vaccination in HIV-infected children, among 39 studies involving >1200 HIV-infected children, none of the study reported death in relation to measles vaccine in HIV-infected children 29 .…”
Section: Discussionmentioning
confidence: 75%
“…However, the geometric mean titer was not statistically different between the three groups. No significant difference in the presence of measles antibody measured by EIA at 6 months of age in children born to HIV-infected and -uninfected mothers was demonstrated in former Zaire [46]. In the United States, only 1 of 23 HIV-infected infants Ͻ6 months of age had maternally acquired measles antibody [13].…”
Section: Clinical Features Of Measles In Hiv-infected Children and Admentioning
confidence: 90%
“…In prospective studies in Rwanda [45] and the former Zaire [46], high-titer EdmonstonZagreb vaccine was administered to HIV-infected children, HIV-uninfected children born to seropositive mothers, and children born to HIV-seronegative mothers. The antibody responses to measles virus at 9 months of age were similar in the three groups, with 76%-94% of children responding to the vaccine.…”
Section: Clinical Features Of Measles In Hiv-infected Children and Admentioning
confidence: 99%
“…Até 1996, os estudos disponíveis na literatura não relatavam aumento de efeitos colaterais da vacina contra o sarampo em pacientes infectados pelo HIV [3][4][5][6][7][8] . A ocorrên-cia de um caso fatal de pneumonite atípica, causada pela cepa vacinal do vírus do sarampo, fez ressurgir a discussão sobre os riscos dessa vacina em soropositivos para o HIV 9 .…”
Section: Introductionunclassified